Primary multifocal squamous cell carcinoma of the breast: A closer look to biological characteristics - Elkiran, Emin Tamer; Aygen, Bilge; Karao?lu, Aziz; Özercan, Ibrahim (UHOD - Uluslararasi Hematoloji Onkoloji Dergisi, 2007)
Primary squamous cell carcinoma (SCC) of the breast is an extremely rare neoplasm. Clinical and biological characteristics are not well-known. There is also no consensus for the adjuvant treatment of this tumor. Herein we present a 37-year-old woman with a diagnosis of multifocal SCC. We also discuss clinical, biological caharacteristics of this rare tumor in the light of pertinent literature.
Keywords: Breast; Chemotherapy; Prognosis; Squamous cell carcinoma